Retrospective analysis of dogs and cats diagnosed with periodontal disease in the Dentistry sector at the University of Franca and the relationship with predisposing factors (Research, Society and Development, 2020)
Periodontal disease is the most commonly diagnosed disease in dogs and cats, being characterized by the involvement of protective tissues and support of dental elements, which form the periodontium. The causative agent is the organized bacterial plaque that, when mineralized, forms the dental calculi, facilitating the progression of the disease. In view of the high incidence of oral diseases in pets and the consequent local and systemic damage, the objective of the present study was to carry out a retrospective study of 335 cases seen in the Veterinary Dentistry of Small Animals sector at the University of Franca, emphasizing those of periodontal disease and, nevertheless, relate them to the review, predisposing factors and classification in degrees. After percentage analyzes, it was observed that 53.3% of the animals were females and 46.7% males and, the majority of the canine specie, being that of the 335 animals, 276 were diagnosed with periodontal disease in degrees varying from mild to severe. In relation to age, most was adults, senile and small, and in terms of race, the mixed breed followed by Poodles were the most affected by periodontal disease. Most tutors offer dry commercial feed; however, with homemade food and, in addition, they do not have the habit of periodically brushing the teeth of these patients. With the data obtained in this retrospection, it is admitted that periodontal disease, in its most varied degrees, is frequently diagnosed in companion animals, especially in small and senile ones, having numerous aggravating factors for its progression and chronicity.